COPPER AND MICROPLASTIC EXPOSURE AFFECTS THE GILL GENE EXPRESSION OF COMMON CARP DURING SALTWATER CHALLENGE - Hoseini, Seyyed M.; Al Sulivany, Basim S.A. (Science Journal of University of Zakho, 2024)
The aim of the present study was to assess if pre-exposure to water copper and/or polyvinyl chloride microparticles affects the transcriptional responses of common carp, Cyprinus carpio, to saltwater exposure. Fish were exposed to 0.25 mg/L copper alone (Cu) or in the presence of 0.5 mg/L polyvinyl chloride microparticles (Cu-MPVC) for 14 days, followed by 72 hours of salt water exposure (0 to 13 ppt NaCl). The copper content in the gills and the expression of heat shock protein (hsp70) and cytochrome P450 family 1 (cyp1a) transcripts were examined. The results showed that gill copper levels increased significantly (P = 0.008) in the Cu and Cu-MPVC treatments after 14 days of exposure, compared to the control fish; the Cu and Cu-MPVC treatments had similar gill copper levels. After 14 days of exposure, branchial expression of the hsp70 and cyp1a genes was significantly up-regulated in the Cu and Cu-MPVC treatments. Exposure to salt water led to a significant down-regulation of the gene transcripts in all treatments after 24 h of exposure. At this point, the Cu and Cu-MPVC treatments showed transcripts similar to those of the control fish prior to saltwater exposure. The fish treated with Cu-MPVC showed significantly higher hsp70 expression 72 h after saltwater exposure than the other treatments. At this time point, the control and Cu fish had significantly lower cyp1a expression than before saltwater exposure. In conclusion, the present data suggest that copper exposure induces stress in the fish gills, and the presence of MPCV in the water hampers normal transcriptomic responses of the fish gills to saltwater exposure.